Local anesthetic systemic toxicity (LAST) during pacemaker implantation through persistent left superior vena cava (PLSVC) - Sunu Budhi Raharjo; Gadistya Novitri Adinda; Dony Yugo Hermanto; Indira Aura Balqis; Dicky Armein Hanafy (Universitas Brawijaya, 2025)
BACKGROUND: Local anesthesia is considered safe and commonly used in the pacemaker implantation procedure. However, it carries a risk of local anesthetic systemic toxicity (LAST). Although rare, LAST occurrence can be fatal. CASE PRESENTATIONS: We reported a case of a 69-year-old woman with fatigue and dizziness. The patient's ECG indicates atrial fibrillation with total AV block. Pacemaker implantation was performed under local anesthesia. Within minutes of lidocaine injection, the patient developed a seizure followed by cardiac arrest. Immediate administration of intravenous midazolam and cardiopulmonary resuscitation was done, resulting in the patient's stability. A permanent pacemaker was successfully implanted using a modified hand-shaped stylet to accommodate the presence of a persistent left superior vena cava (PLSVC). Brain computed tomography scan showed only mild brain atrophy. No clinical symptoms were documented during the outpatient visit after discharge. CONCLUSIONS: Local anesthetic systemic toxicity during pacemaker implantation is a rare but potentially catastrophic. Prompt recognition of its signs and appropriate management are crucial. In this case, a persistent left superior vena cava posed additional challenges to the pacemaker implantation.